The Role Of Leadership In Employee Prosperity Pt Dakka Opa East Energy - Nurhapsa, Nurhapsa; Kusdarianto, Indra; Suardi, Ahmad (Review of Accounting and Taxation, 2024)
Purpose - Leaders have a very important role in determining the direction of success in an organization. Through effective leadership, leaders are able to form a positive work culture, motivate employees, and encourage overall organizational performance.One important aspect of leadership is how leaders are able to improve the welfare of their employees. Design/methodology/approach - The method used is simple regression analysis. The data used are primary data and secondary data obtained from the results of distributing questionnaires and observations in the field. The results of the simple regression analysis of this research prove that by looking at the calculated F of 17.930 with a significance level of 0.000 < 0.005, it shows that the regression model used is valid and can be used to predict the influence of the leadership variable (X) on the employee welfare variable (Y). that is, there is strong evidence that leadership has an influence on employee well-being.. Finding - The correlation value (R) between leadership variables and employee welfare is 0.566. This value shows that there is a moderate relationship between these two variables. In other words, changes in leadership variables will have an impact on changes in employee welfare variables. The coefficient of determination (R Square) of 0.321 or 32.1% shows that the leadership variable contributes 32.1% to the employee welfare variable. This means that about a third of the variation in employee well-being can be explained by variation in leadership. Originality - The novelty of this research is deeper understanding of leadership styles and employee welfare due to less effective communication in the work environment. By digging deeper into these factors, this research can provide valuable insight for company management, leaders and employees so they can be more effective.